Enhancing the Performance of Indoor Device-Free Passive Localization - Wu Yang; Liangyi Gong; Dapeng Man; Jiguang Lv; Haibin Cai; Xiancun Zhou; Zheng Yang (International Journal of Distributed Sensor Networks)
Device-free passive localization (DFPL) has been an emerging application with fast increasing development. Channel State Information- (CSI-) based DFPL is recently paid more attention to for fine-granularity and stability of CSI. However, lots of dead spots exist in the area of interest. And the accuracy of localization is not still completely satisfactory, especially for outside of the first Fresnel zone. In our paper, we put forward a new metric to estimate the sensitivity of a receiver to changes in the detecting area. In our experiment, we observe that the performance of DFPL can be raised when the receiver is placed at the location with high receiver sensitivity. Hence, we develop a new high-performance indoor device-free passive localization (HiDFPL), which employs a Bayesian a posteriori approach and possesses high receiver sensitivity. The experiment results demonstrate the outstanding performance of the proposed scheme.